The Influence of Service Quality on the Decline In Tourist Visits at the Maimun Palace in Medan City - Sitanggang, Benni; Ashiilah, Tara; Ardini, Putri; Simatupang, Jernita; Tarigan, Josua Vatrick (International Journal of Education, Information Technology, and Others, 2023)
This research investigates the decline in visitation at Medan City's Maimun Palace by emphasizing the influence of declining service quality, particularly regarding noise and the lack of separation between the merchant area and historical relics. Involving qualitative and descriptive research methods, analysis of the findings highlighted the need for improved layout, implementation of strict regulations on merchants, and enhancement of tourist services as integral solutions. The results show that these improvements are expected to create a clearer flow of visits, maintain the quality of the destination, and provide a more satisfying visitor experience. The conclusions emphasize the urgency of integrated measures to support sustainability and restore visitor interest, while recognizing that the focus on service aspects is a limitation. These measures provide a basis for further efforts to develop and improve the management of this historic tourist destination.